Heat-treatment-free high-temperature-resistant wear-resistant high-toughness aluminum alloy
By adding elements such as La, Cu, Sn, Cd, Ge, etc. to the aluminum alloy, and using vacuum die-casting and cathode plasma discharge oxidation treatment, the problem of poor wear performance of traditional aluminum alloys at high temperatures and achieving high strength and wear resistance The production process is greatly improved and the production process is simplified, suitable for the manufacturing of high-performance components.
Patent Information
- Application Number
- CN202411614573.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2024-12-27
AI Technical Summary
Traditional Al-Si die-cast aluminum alloys have poor performance in high temperatures and wear, and are complex in process, which limits their use in industrial applications.
The alloys of La, Cu, Sn, Cd, Ge and other elements are composed of alloys, combined with vacuum die-casting and cathode plasma discharge oxidation treatment, and a high-strength aluminum alloy with heat-free treatment is realized. The fine Al11La3 phase is formed by La, and the θ-Al2Cu phase is precipitated. Sn and Cd are oxidized in situ to form ceramic phases, improving the wear resistance and high temperature performance of the alloy.
It has achieved the improvement of high strength, wear resistance and high temperature performance, while simplified production processes and reduced costs, and is suitable for high-performance components such as new energy vehicle motor case.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of aluminum alloy development, and specifically relates to a high-temperature, wear-resistant, high-strength and tough aluminum alloy that does not require heat treatment. Background Art
[0002] Die casting is a manufacturing process that involves rapidly injecting molten metal into a mold under high pressure and rapidly solidifying the alloy under high pressure. It is mainly used to produce metal parts. Die casting is widely used in the large-scale production of automotive pistons and other parts because of its one-step molding, high production efficiency, high dimensional accuracy, and the ability to produce complex parts with extremely small tolerances, high material utilization, less waste, and good surface quality, smooth and defect-free. With the advancement of industrial production and the improvement of product quality requirements, higher quality requirements have been put forward for the performance and process of cast aluminum alloys.
[0003] Optimizing the mechanical properties and high temperature performance of die-cast aluminum alloys is usually achieved by adding elements to change the phase structure of the alloy and optimizing the die-casting post-processing process. CN118345283 A discloses a heat-treatment-free high-strength aluminum alloy with relatively poor mechanical properties and no optimization of high temperature performance and wear resistance.
[0004] At present, Al-Si die-cast aluminum alloys are widely used, in which elements such as Cu, Mg, and Zn are added to improve strength, and about 1.0% of Fe is contained to reduce the tendency of "sticking to the mold" during the die-casting process. Because the traditional Al-Si die-cast aluminum alloy contains 6-11% Si elements to ensure that the alloy has excellent casting formability, it contains a large amount of eutectic Si crystallized and precipitated during the solidification process. The Si phase has low strength and is brittle. It is easy to produce microcracks and induce alloy fracture during the load process. Therefore, this type of alloy has limited strength in the die-cast state. In addition, because the traditional die-cast aluminum alloy contains a high Fe content, Fe has a very low solid solubility in the aluminum alloy matrix grains. During the solidification process, it combines with Al, Si and other elements to precipitate to form a needle-like iron-rich phase. Although this phase is relatively hard, its needle-like shape has a splitting effect on the aluminum alloy matrix grains, and stress concentration is easy to form microcracks at its edges to induce alloy fracture. Therefore, the plasticity of this type of alloy in the die-cast state is usually low. The above-mentioned shortcomings and deficiencies limit the application of traditional Al-Si die-casting aluminum alloy materials. Therefore, in order to adapt to the development of the manufacturing industry, there is an urgent need for high-strength and tough heat-treatment-free aluminum alloys with excellent casting formability, high strength and plasticity. Summary of the invention
[0005] The object of the present invention is to overcome at least one shortcoming of the prior art and to provide a high-temperature, wear-resistant, high-strength and tough aluminum alloy that does not require heat treatment.
[0006] The technical solution adopted by the present invention is: In a first aspect, the present invention provides a heat-treatment-free, high-temperature-resistant, wear-resistant, high-strength and toughness aluminum alloy. The alloy composition, in mass percentage, is: La 7.8-8.4%, Cu 1.2-2.4%, Sn 3.9-4.4%, Cd 2.1-2.4%, Ge0.8-1.1%, and the remainder is Al.
[0007] In some examples, the mass percentage content of La is 8.1-8.3%.
[0008] In some examples, the mass percentage content of Cu is: 2.1-2.2%.
[0009] In some examples, the mass percentage content of Sn is: 4.1-4.3%.
[0010] In some examples, the mass percentage content of Cd is: 2.1-2.3%.
[0011] In some examples, the mass percentage content of Ge is: 0.85-0.95%.
[0012] In a second aspect, the method for preparing the heat-treatment-free high-temperature-resistant, wear-resistant, high-strength and tough aluminum alloy provided in the first aspect of the present invention comprises the following steps: 1) Weigh the raw materials according to the alloy composition, melt them into aluminum alloy liquid at 710℃~740℃, remove the slag and stir evenly; 2) Refining is performed under a protective gas atmosphere at 710°C to 740°C, stirring for 5 to 20 minutes, and keeping warm for 20 to 30 minutes, removing slag and filtering, and performing dehydrogenation treatment to obtain an alloy ingot; 3) taking the alloy ingot prepared in step 2) and performing vacuum die casting; 4) The die-cast ingot is water quenched to room temperature, and subjected to cathode plasma discharge oxidation treatment and natural aging treatment to obtain the heat-treatment-free, high-temperature, wear-resistant, high-strength and tough aluminum alloy.
[0013] In some examples, the vacuum die-casting parameters of step 3) are: pouring temperature of 690-700°C, mold temperature of 350-400°C, vacuum degree of 400-500 mbar, filling speed of 30-35 m / s, boost pressure of 1400-1500 bar, and holding time of 8-10 s.
[0014] In some examples, the parameters of the natural aging treatment in step 4) are: placing at 20-25° C. for at least 120 hours.
[0015] In a third aspect, the heat-treatment-free, high-temperature-resistant, wear-resistant, high-strength and toughness aluminum alloy provided in the first aspect of the present invention is used in the preparation of motor casings.
[0016] The beneficial effects of the present invention are: Aiming at reducing the production cost of aluminum alloy and simplifying the production process while maintaining high performance, the present invention invents a high-strength and toughness die-cast Al-La-Cu-Sn-Cd-Ge alloy that does not require heat treatment. The alloy has high strength, excellent wear resistance and high-temperature mechanical properties, low production cost, and simple process flow. It can be used to make motor housings for new energy vehicles, meeting the requirements for alloy strength and high-temperature performance.
[0017] The heat-treatment-free, high-temperature, wear-resistant, high-strength and tough aluminum alloy of the present invention mainly adds a considerable amount of La element content in the alloy. La is a light rare earth element with extremely low solid solubility in the aluminum matrix. It often exists in the form of a second phase, which can delay the grain growth and structural softening of the alloy at high temperatures, and effectively improve the high-temperature creep resistance of the alloy. At the same time, La can lower the melting point of the aluminum alloy, thereby improving the fluidity of the alloy and improving the accuracy of the die-casting process. When the La content in the alloy is between 7.8% and 8.4%, La forms Al with Al. 11 La3 phase. Fine dispersed Al 11 La3 phase, as the second phase with the largest number in the alloy of the present invention, has a strengthening effect on the alloy strength. The reason is that the enrichment of La element at the front of the solidification interface will cause the composition to be supercooled. At the same time, α-Al and Al 11 The mismatch degree of La3 phase is low, making Al 11 La3 can serve as a heterogeneous nucleation site for the α-Al phase, and the two can jointly promote grain refinement.
[0018] Cu is usually used in aluminum alloys to strengthen the alloy through two methods: solid solution and aging. Adding Cu can precipitate a strengthening phase θ-Al2Cu in the alloy. This phase is small and evenly distributed, which can effectively hinder dislocation movement and comprehensively improve the strength of the alloy.
[0019] Sn will form Al-Sn eutectic with Al in the alloy at 228℃. Since the solid solubility between Al and Sn is very low, Sn tends to precipitate in the aluminum matrix in the form of granular Sn phase. The presence of these Sn particles usually presents a softer dispersed phase, which helps to reduce friction and wear. Due to its granular or layered shape characteristics, Sn will not significantly affect the strength of the alloy while improving the wear resistance of Al alloy. In addition, Sn can be in-situ oxidized to generate SnO2 after plasma electrolysis, and combined with Al2O3 in the aluminum matrix to form Al2O3·SnO2 ceramic phase, which can effectively improve the wear resistance of the ingot.
[0020] Cd has a similar effect to Sn. It will be in-situ oxidized into CdO under high pressure and combine with Al2O3·SnO2 to form Al2O3·SnO2·CdO, which can effectively improve the wear resistance of the alloy.
[0021] Ge can effectively reduce the melting point of the alloy, improve the fluidity of the alloy, and can more effectively improve the casting performance of the alloy.
[0022] The present invention realizes rapid solid solution of elements in the alloy through high temperature during die casting, and then naturally ages the alloy at room temperature for 120 hours after rapid cooling in ice water, so that the strengthening phase in the alloy is precipitated. This process allows the alloy to effectively precipitate the second phase that plays a strengthening role while eliminating the heat treatment process, thus streamlining the production process and controlling the production cost.
[0023] The present invention uses cathode plasma discharge oxidation to in-situ oxidize Al, Sn, and Cd on the alloy surface to generate a denser Al2O3·SnO2·CdO oxide layer, which greatly improves the wear resistance of the ingot. Compared with anodic oxidation, the oxide film produced is denser and smoother, and the current density required in production is lower. DETAILED DESCRIPTION
[0024] The following disclosure provides many different embodiments or examples for implementing different solutions of the present invention.
[0025] The chemical composition weight percentage of the alloy in each embodiment is La 7.8-8.4%, Cu 1.2-2.4%, Sn 3.9-4.4%, Cd 2.1-2.4%, Ge 0.8-1.1%. The raw materials are selected from Al-La master alloy, Al-Cu master alloy, Al-Sn master alloy, Al-Cd master alloy, and Al-Ge master alloy.
[0026] Table 1 Chemical composition of the embodiments and comparative examples (mass percentage)
[0027] The preparation methods of the embodiments and comparative examples are as follows: Raw material preparation: weigh pure Al, Al-La, Al-Cu, Al-Sn, Al-Cd, Al-Ge master alloys in proportion for smelting; Melting and casting: the aluminum ingot and aluminum master alloy weighed in step 1) are put into a melting furnace for heating and melting, and after removing the slag, they are stirred evenly, refined with a protective gas mixed with SO2 and N2, dehydrogenated, and the slag is allowed to stand and filter to obtain an alloy melt; Die casting: take the aluminum alloy solution obtained in step 2), let it stand for 15 minutes, and then die cast at 690°C; Aging: The aluminum alloy obtained in step 3) is placed in ice water and quenched to room temperature, and naturally aged at room temperature for 120 hours to obtain the target heat-treatment-free, high-temperature, wear-resistant, high-strength and tough die-cast aluminum alloy.
[0028] Preferably, the alloy melting temperature is 710°C to 740°C, and the refining temperature is 710°C to 740°C.
[0029] Preferably, a mixed gas consisting of argon with a purity of 99.99% and chlorine with a purity of 99.99% is introduced into the aluminum alloy liquid by bubbling for 15 minutes for dehydrogenation treatment, the volume percentage of chlorine in the mixed gas is 10%, and the flow rate of the mixed gas is 1m 3 / min.
[0030] Preferably, during vacuum die casting, the pouring temperature of the aluminum alloy liquid is 690°C, the mold temperature is 350-400°C, the vacuum degree is 400-500mbar, the filling speed is 30-35m / s, the boost pressure is 1400-1500bar, and the holding time is 8-10s. Through vacuum die casting with these parameters, a high-strength and tough die-cast aluminum alloy with dense structure and complete filling can be obtained, and the obtained die-cast aluminum alloy has the properties of high strength and high plasticity.
[0031] Preferably, the obtained ingot is subjected to cathode plasma electrolytic oxidation treatment, with metal platinum as the anode, the obtained ingot as the cathode, the electrolyte being a 40% glycerol aqueous solution, and discharged at a voltage of 340 to 400 V for 5 minutes to obtain an Al2O3·SnO2·CdO surface oxide layer on the alloy surface.
[0032] Preferably, the natural aging time is 120 hours at room temperature of 25°C.
[0033] The post-processing processes of die casting of various embodiments and comparative examples are shown in Table 2.
[0034] Table 2 Comparison of subsequent treatment processes of the embodiment and the comparative example
[0035] Multiple refining agents and degassing agents can be added during the smelting process. Multiple refining agents and degassing agents are commonly used in the field, and the mass ratio of refining agent to smelting ingredients is (1-3):100. The composition of the multiple composite refining agent includes: 20wt% NaCl, 20wt% KCl, 35wt% NaF, 25wt% LiF; the mass ratio of degassing agent to smelting ingredients is 1:100, and the degassing agent is Ar+Cl2 mixed gas. Multiple refining agents and degassing agents themselves have basically no effect on the properties of the alloy. Comparison of properties of different die-casting aluminum alloys
[0036] The alloys obtained in the examples and comparative examples were tested for performance and mechanical properties. The test methods for strength and elongation were determined according to GB / T 228.1-2010 "Metallic material tensile test Part 1: Room temperature test method"; the test method for high temperature performance was determined according to GB / T 4338-2006 "Metallic material high temperature tensile test method"; the test method for wear resistance was determined according to GB / T12444-2006 "Metallic material wear test method test ring-test block sliding wear test".
[0037] Table 3 Performance test results of various embodiments and comparative examples
[0038] In summary, the present invention selects La as the main element of the alloy, adds Cu, Sn, Cd elements and optimizes the die-casting process and subsequent treatment process, so that the grains in the alloy are refined, and the second phase that improves the metal mechanical properties, wear resistance and high temperature performance is fully precipitated in the alloy, thereby giving the alloy higher toughness and excellent heat resistance and wear resistance. The aluminum alloy provided by the present invention has a tensile strength of ≥280MPa, a yield strength of ≥220MPa, and an elongation of ≥14%. At 350°C, the tensile strength of the alloy is ≥235MPa, the yield strength is ≥200MPa, and the elongation is ≥16%. The wear rate at room temperature is 5.56×10 -4 ±0.2mm 3 / (N·m), the wear rate at 350℃ is 10.4×10 -4 ±0.4mm 3 / (N·m).
[0039] The above is a further detailed description of the present invention, which should not be regarded as a limitation on the specific implementation of the present invention. For ordinary technicians in the technical field to which the present invention belongs, simple deduction or replacement without departing from the concept of the present invention is within the protection scope of the present invention.
Claims
1. A heat-treatment-free, high-temperature, wear-resistant, high-strength and tough aluminum alloy, characterized in that: In terms of mass percentage, the composition of the alloy is: La 7.8-8.4%, Cu 1.2-2.4%, Sn 3.9-4.4%, Cd 2.1-2.4%, Ge 0.8-1.1%, and the balance is Al.
2. The heat-treatment-free, high-temperature, wear-resistant, high-strength and tough aluminum alloy according to claim 1, characterized in that: The mass percentage content of La is 8.1-8.3%.
3. The heat-treatment-free, high-temperature-resistant, wear-resistant, high-strength and tough aluminum alloy according to claim 1, characterized in that: The mass percentage content of Cu is: 2.1-2.2%.
4. The heat-treatment-free high-temperature-resistant, wear-resistant, high-strength and tough aluminum alloy according to claim 1, characterized in that: The mass percentage content of Sn is: 4.1-4.3%.
5. The heat-treatment-free high-temperature-resistant, wear-resistant, high-strength and tough aluminum alloy according to claim 1, characterized in that: The mass percentage content of Cd is: 2.1-2.3%.
6. The heat-treatment-free high-temperature-resistant, wear-resistant, high-strength and tough aluminum alloy according to claim 1, characterized in that: The mass percentage content of Ge is: 0.85-0.95%.
7. The method for preparing the heat-treatment-free high-temperature-resistant, wear-resistant, high-strength and tough aluminum alloy according to any one of claims 1 to 6, characterized in that: The following steps are involved: 1) Weigh the raw materials according to the alloy composition, melt them into aluminum alloy liquid at 710℃~740℃, remove the slag and stir evenly; 2) Refining is performed under a protective gas atmosphere at 710°C to 740°C, stirring for 5 to 20 minutes, and keeping warm for 20 to 30 minutes, removing slag and filtering, and performing dehydrogenation treatment to obtain an alloy ingot; 3) taking the alloy ingot prepared in step 2) and performing vacuum die casting; 4) The die-cast ingot is water quenched to room temperature, and subjected to cathode plasma discharge oxidation treatment and natural aging treatment to obtain the heat-treatment-free, high-temperature, wear-resistant, high-strength and tough aluminum alloy.
8. The preparation method according to claim 7, characterized in that: The vacuum die-casting parameters of step 3) are: pouring temperature of 690-700°C, mold temperature of 350-400°C, vacuum degree of 400-500 mbar, filling speed of 30-35 m / s, boost pressure of 1400-1500 bar, and holding time of 8-10 s.
9. The preparation method according to claim 7, characterized in that: The parameters of the natural aging treatment in step 4) are: placing at 20-25°C for at least 120 hours.
10. Use of the heat-treatment-free, high-temperature-resistant, wear-resistant, high-strength and toughness aluminum alloy according to any one of claims 1 to 6 in the preparation of motor housings.
